Remove the concept of an `LTuple`.

finite-set-exercises
Joshua Potter 2023-05-13 09:23:44 -06:00
parent e1af33e805
commit 708295f53f
5 changed files with 2 additions and 549 deletions

View File

@ -29,7 +29,7 @@ Then $x_1 = \langle y_1, \ldots, y_{k+1} \rangle$.
\begin{proof} \begin{proof}
\lean{Bookshelf/Enderton/Chapter\_0}{Enderton.Chapter\_0.lemma\_0a} TODO
\end{proof} \end{proof}

View File

@ -1,5 +1,3 @@
import Common.LTuple.Basic
/-! # Enderton.Chapter_0 /-! # Enderton.Chapter_0
Useful Facts About Sets Useful Facts About Sets
@ -7,272 +5,6 @@ Useful Facts About Sets
namespace Enderton.Chapter_0 namespace Enderton.Chapter_0
/-- -- TODO
The following describes a so-called "generic" tuple. Like an `LTuple`, a generic
`n`-tuple is defined recursively like so:
`⟨x₁, ..., xₙ⟩ = ⟨⟨x₁, ..., xₙ₋₁⟩, xₙ⟩`
Unlike `LTuple`, this tuple bends the syntax above further. For example,
both tuples above are equivalent to:
`⟨⟨x₁, ..., xₘ⟩, xₘ₊₁, ..., xₙ⟩`
for some `1 ≤ m ≤ n`. This distinction is purely syntactic, and introduced
solely to prove `lemma_0a`. In other words, `LTuple` is an always-normalized
variant of an `GTuple`. In general, prefer it over this when working within
Enderton's book.
-/
inductive GTuple : (α : Type u) → (size : Nat × Nat) → Type u where
| nil : GTuple α (0, 0)
| snoc : GTuple α (p, q) → LTuple α r → GTuple α (p + q, r)
syntax (priority := high) "t[" term,* "]" : term
macro_rules
| `(t[]) => `(LTuple.nil)
| `(t[$x]) => `(LTuple.snoc t[] $x)
| `(t[$xs:term,*, $x]) => `(LTuple.snoc t[$xs,*] $x)
syntax (priority := high) "g[" term,* "]" : term
macro_rules
| `(g[]) => `(GTuple.nil)
| `(g[$x]) => `(GTuple.snoc g[] t[$x])
| `(g[g[$xs:term,*], $ys:term,*]) => `(GTuple.snoc g[$xs,*] t[$ys,*])
| `(g[$x, $xs:term,*]) => `(GTuple.snoc g[] t[$x, $xs,*])
namespace GTuple
open scoped LTuple
/-! ## Normalization -/
/--
Converts an `GTuple` into "normal form".
-/
def norm : GTuple α (m, n) → LTuple α (m + n)
| g[] => t[]
| snoc is ts => LTuple.concat is.norm ts
/--
Normalization of an empty `GTuple` yields an empty `Tuple`.
-/
theorem norm_nil_eq_nil : @norm α 0 0 nil = LTuple.nil :=
rfl
/--
Normalization of a pseudo-empty `GTuple` yields an empty `Tuple`.
-/
theorem norm_snoc_nil_nil_eq_nil : @norm α 0 0 (snoc g[] t[]) = t[] := by
unfold norm norm
rfl
/--
Normalization elimates `snoc` when the `snd` component is `nil`.
-/
theorem norm_snoc_nil_elim {t : GTuple α (p, q)}
: norm (snoc t t[]) = norm t := by
cases t with
| nil => simp; unfold norm norm; rfl
| snoc tf tl =>
simp
conv => lhs; unfold norm
/--
Normalization eliminates `snoc` when the `fst` component is `nil`.
-/
theorem norm_nil_snoc_elim {ts : LTuple α n}
: norm (snoc g[] ts) = cast (by simp) ts := by
unfold norm norm
rw [LTuple.nil_concat_self_eq_self]
/--
Normalization distributes across `Tuple.snoc` calls.
-/
theorem norm_snoc_snoc_norm
: norm (snoc as (LTuple.snoc bs b)) = LTuple.snoc (norm (snoc as bs)) b := by
unfold norm
rw [← LTuple.concat_snoc_snoc_concat]
/--
Normalizing an `GTuple` is equivalent to concatenating the normalized `fst`
component with the `snd`.
-/
theorem norm_snoc_eq_concat {t₁ : GTuple α (p, q)} {t₂ : LTuple α n}
: norm (snoc t₁ t₂) = LTuple.concat t₁.norm t₂ := by
conv => lhs; unfold norm
/-! ## Equality -/
/--
Implements Boolean equality for `GTuple α n` provided `α` has decidable
equality.
-/
instance BEq [DecidableEq α] : BEq (GTuple α n) where
beq t₁ t₂ := t₁.norm == t₂.norm
/-! ## Basic API -/
/--
Returns the number of entries in the `GTuple`.
-/
def size (_ : GTuple α n) := n
/--
Returns the number of entries in the "shallowest" portion of the `GTuple`. For
example, the length of `x[x[1, 2], 3, 4]` is `3`, despite its size being `4`.
-/
def length : GTuple α n → Nat
| g[] => 0
| snoc g[] ts => ts.size
| snoc _ ts => 1 + ts.size
/--
Returns the first component of our `GTuple`. For example, the first component of
tuple `x[x[1, 2], 3, 4]` is `t[1, 2]`.
-/
def fst : GTuple α (m, n) → LTuple α m
| g[] => t[]
| snoc ts _ => ts.norm
/--
Given `GTuple α (m, n)`, the `fst` component is equal to an initial segment of
size `k` of the tuple in normal form.
-/
theorem self_fst_eq_norm_take (t : GTuple α (m, n)) : t.fst = t.norm.take m :=
match t with
| g[] => by
unfold fst
rw [LTuple.self_take_zero_eq_nil]
simp
| snoc tf tl => by
unfold fst
conv => rhs; unfold norm
rw [LTuple.eq_take_concat]
simp
/--
If the normal form of an `GTuple` is equal to a `Tuple`, the `fst` component
must be a prefix of the `Tuple`.
-/
theorem norm_eq_fst_eq_take {t₁ : GTuple α (m, n)} {t₂ : LTuple α (m + n)}
: (t₁.norm = t₂) → (t₁.fst = t₂.take m) := by
intro h
rw [self_fst_eq_norm_take, h]
/--
Returns the first component of our `GTuple`. For example, the first component of
tuple `x[x[1, 2], 3, 4]` is `t[3, 4]`.
-/
def snd : GTuple α (m, n) → LTuple α n
| g[] => t[]
| snoc _ ts => ts
end GTuple
/-! ## Lemma 0A -/
section
variable {k m n : Nat}
variable (p : 1 ≤ m)
variable (q : n + (m - 1) = m + k)
private lemma n_eq_succ_k : n = k + 1 := by
let ⟨m', h⟩ := Nat.exists_eq_succ_of_ne_zero $ show m ≠ 0 by
intro h
have ff : 1 ≤ 0 := h ▸ p
ring_nf at ff
exact ff.elim
calc
n = n + (m - 1) - (m - 1) := by rw [Nat.add_sub_cancel]
_ = m' + 1 + k - (m' + 1 - 1) := by rw [q, h]
_ = m' + 1 + k - m' := by simp
_ = 1 + k + m' - m' := by rw [Nat.add_assoc, Nat.add_comm]
_ = 1 + k := by simp
_ = k + 1 := by rw [Nat.add_comm]
private lemma n_pred_eq_k : n - 1 = k := by
have h : k + 1 - 1 = k + 1 - 1 := rfl
conv at h => lhs; rw [←n_eq_succ_k p q]
simp at h
exact h
private lemma n_geq_one : 1 ≤ n := by
rw [n_eq_succ_k p q]
simp
private lemma min_comm_succ_eq : min (m + k) (k + 1) = k + 1 :=
Nat.recOn k
(by simp; exact p)
(fun k' ih => calc min (m + (k' + 1)) (k' + 1 + 1)
_ = min (m + k' + 1) (k' + 1 + 1) := by conv => rw [Nat.add_assoc]
_ = min (m + k') (k' + 1) + 1 := Nat.min_succ_succ (m + k') (k' + 1)
_ = k' + 1 + 1 := by rw [ih])
private lemma n_eq_min_comm_succ : n = min (m + k) (k + 1) := by
rw [min_comm_succ_eq p]
exact n_eq_succ_k p q
private lemma n_pred_m_eq_m_k : n + (m - 1) = m + k := by
rw [←Nat.add_sub_assoc p, Nat.add_comm, Nat.add_sub_assoc (n_geq_one p q)]
conv => lhs; rw [n_pred_eq_k p q]
private def castNorm : GTuple α (n, m - 1) → LTuple α (m + k)
| xs => cast (by rw [q]) xs.norm
private def castFst : GTuple α (n, m - 1) → LTuple α (k + 1)
| xs => cast (by rw [n_eq_succ_k p q]) xs.fst
private def castTake (ys : LTuple α (m + k)) :=
cast (by rw [min_comm_succ_eq p]) (ys.take (k + 1))
/-- #### Lemma 0A
Assume that `⟨x₁, ..., xₘ⟩ = ⟨y₁, ..., yₘ, ..., yₘ₊ₖ⟩`. Then
`x₁ = ⟨y₁, ..., yₖ₊₁⟩`.
-/
theorem lemma_0a (xs : GTuple α (n, m - 1)) (ys : LTuple α (m + k))
: (castNorm q xs = ys) → (castFst p q xs = castTake p ys) := by
intro h
suffices HEq
(cast (_ : LTuple α n = LTuple α (k + 1)) xs.fst)
(cast (_ : LTuple α (min (m + k) (k + 1)) = LTuple α (k + 1)) (LTuple.take ys (k + 1)))
from eq_of_heq this
congr
· exact n_eq_min_comm_succ p q
· rfl
· exact n_eq_min_comm_succ p q
· exact HEq.rfl
· exact Eq.recOn
(motive := fun _ h => HEq
(_ : n + (n - 1) = n + k)
(cast h (show n + (n - 1) = n + k by rw [n_pred_eq_k p q])))
(show (n + (n - 1) = n + k) = (min (m + k) (k + 1) + (n - 1) = n + k) by
rw [n_eq_min_comm_succ p q])
HEq.rfl
· exact n_geq_one p q
· exact n_pred_eq_k p q
· exact Eq.symm (n_eq_min_comm_succ p q)
· exact n_pred_eq_k p q
· rw [GTuple.self_fst_eq_norm_take]
unfold castNorm at h
simp at h
rw [←h, ←n_eq_succ_k p q]
have h₂ := Eq.recOn
(motive := fun x h => HEq
(LTuple.take xs.norm n)
(LTuple.take (cast (show LTuple α (n + (m - 1)) = LTuple α x by rw [h]) xs.norm) n))
(show n + (m - 1) = m + k by rw [n_pred_m_eq_m_k p q])
HEq.rfl
exact Eq.recOn
(motive := fun x h => HEq
(cast h (LTuple.take xs.norm n))
(LTuple.take (cast (_ : LTuple α (n + (m - 1)) = LTuple α (m + k)) xs.norm) n))
(show LTuple α (min (n + (m - 1)) n) = LTuple α n by simp)
h₂
end
end Enderton.Chapter_0 end Enderton.Chapter_0

View File

@ -1,5 +1,4 @@
import Common.Combinator import Common.Combinator
import Common.List import Common.List
import Common.LTuple
import Common.Real import Common.Real
import Common.Set import Common.Set

View File

@ -1 +0,0 @@
import Common.LTuple.Basic

View File

@ -1,277 +0,0 @@
import Mathlib.Tactic.Ring
/-! # Common.LTuple.Basic
The following is a representation of a (possibly empty) left-biased tuple. A
left-biased `n`-tuple is defined recursively as follows:
```
⟨x₁, ..., xₙ⟩ = ⟨⟨x₁, ..., xₙ₋₁⟩, xₙ⟩
```
Note a `Tuple` exists in Lean already. This implementation differs in two
notable ways:
1. It is left-associative. The built-in `Tuple` instance evaluates e.g.
`(x₁, x₂, x₃)` as `(x₁, (x₂, x₃))` instead of `((x₁, x₂), x₃)`.
2. Internally, the built-in `Tuple` instance is syntactic sugar for nested
`Prod` instances. Unlike this implementation, an `LTuple` is a homogeneous
collection.
In general, prefer using `Prod` over `LTuple`. This exists primarily to solve
certain theorems outlined in [^1].
[^1]: Enderton, Herbert B. A Mathematical Introduction to Logic. 2nd ed. San
Diego: Harcourt/Academic Press, 2001.
-/
/--
#### LTuple
A left-biased, possibly empty, homogeneous `Tuple`-like structure..
-/
inductive LTuple : (α : Type u) → (size : Nat) → Type u where
| nil : LTuple α 0
| snoc : LTuple α n → α → LTuple α (n + 1)
namespace LTuple
/-! ## Coercions -/
scoped instance : CoeOut (LTuple α (min (m + n) m)) (LTuple α m) where
coe := cast (by simp)
scoped instance : Coe (LTuple α 0) (LTuple α (min n 0)) where
coe := cast (by rw [Nat.min_zero])
scoped instance : Coe (LTuple α 0) (LTuple α (min 0 n)) where
coe := cast (by rw [Nat.zero_min])
scoped instance : Coe (LTuple α n) (LTuple α (min n n)) where
coe := cast (by simp)
scoped instance : Coe (LTuple α n) (LTuple α (0 + n)) where
coe := cast (by simp)
scoped instance : Coe (LTuple α (min m n + 1)) (LTuple α (min (m + 1) (n + 1))) where
coe := cast (by rw [Nat.min_succ_succ])
scoped instance : Coe (LTuple α m) (LTuple α (min (m + n) m)) where
coe := cast (by simp)
/-! ### Equality -/
/--
Two values `a` and `b` are equal **iff** `[a] = [b]`.
-/
theorem eq_iff_singleton : (a = b) ↔ (snoc a nil = snoc b nil) := by
apply Iff.intro
· intro h; rw [h]
· intro h; injection h
/--
Two lists are equal **iff** their heads and tails are equal.
-/
theorem eq_iff_snoc {t₁ t₂ : LTuple α n}
: (a = b ∧ t₁ = t₂) ↔ (snoc t₁ a = snoc t₂ b) := by
apply Iff.intro
· intro ⟨h₁, h₂ ⟩; rw [h₁, h₂]
· intro h
injection h with _ h₁ h₂
exact And.intro h₂ h₁
/--
Implements decidable equality for `Tuple α m`, provided `a` has decidable
equality.
-/
protected def hasDecEq [DecidableEq α] (t₁ t₂ : LTuple α n)
: Decidable (Eq t₁ t₂) :=
match t₁, t₂ with
| nil, nil => isTrue rfl
| snoc as a, snoc bs b =>
match LTuple.hasDecEq as bs with
| isFalse np => isFalse (fun h => absurd (eq_iff_snoc.mpr h).right np)
| isTrue hp =>
if hq : a = b then
isTrue (eq_iff_snoc.mp $ And.intro hq hp)
else
isFalse (fun h => absurd (eq_iff_snoc.mpr h).left hq)
instance [DecidableEq α] : DecidableEq (LTuple α n) := LTuple.hasDecEq
/-! ## Basic API -/
/--
Returns the number of entries in an `LTuple`.
-/
def size (_ : LTuple α n) : Nat := n
/--
Returns all but the last entry of an `LTuple`.
-/
def init : (t : LTuple α (n + 1)) → LTuple α n
| snoc vs _ => vs
/--
Returns the last entry of an `LTuple`.
-/
def last : LTuple α (n + 1) → α
| snoc _ v => v
/--
Prepends an entry to an `LTuple`.
-/
def cons : LTuple α n → α → LTuple α (n + 1)
| nil, a => snoc nil a
| snoc ts t, a => snoc (cons ts a) t
/-! ## Concatenation -/
/--
Joins two `LTuple`s together end to end.
-/
def concat : LTuple α m → LTuple α n → LTuple α (m + n)
| is, nil => is
| is, snoc ts t => snoc (concat is ts) t
/--
Concatenating an `LTuple` with `nil` yields the original `LTuple`.
-/
theorem self_concat_nil_eq_self (t : LTuple α m) : concat t nil = t :=
match t with
| nil => rfl
| snoc _ _ => rfl
/--
Concatenating `nil` with an `LTuple` yields the original `LTuple`.
-/
theorem nil_concat_self_eq_self (t : LTuple α m) : concat nil t = t := by
induction t with
| nil => unfold concat; simp
| @snoc n as a ih =>
unfold concat
rw [ih]
suffices HEq (snoc (cast (_ : LTuple α n = LTuple α (0 + n)) as) a) ↑(snoc as a)
from eq_of_heq this
have h₁ := Eq.recOn
(motive := fun x h => HEq
(snoc (cast (show LTuple α n = LTuple α x by rw [h]) as) a)
(snoc as a))
(show n = 0 + n by simp)
HEq.rfl
exact Eq.recOn
(motive := fun x h => HEq
(snoc (cast (_ : LTuple α n = LTuple α (0 + n)) as) a)
(cast h (snoc as a)))
(show LTuple α (n + 1) = LTuple α (0 + (n + 1)) by simp)
h₁
/--
Concatenating an `LTuple` to a nonempty `LTuple` moves `concat` calls closer to
the expression leaves.
-/
theorem concat_snoc_snoc_concat {bs : LTuple α n}
: concat as (snoc bs b) = snoc (concat as bs) b :=
rfl
/--
`snoc` is equivalent to concatenating the `init` and `last` elements of an
`LTuple` together.
-/
theorem snoc_eq_init_concat_last (as : LTuple α m)
: snoc as a = concat as (snoc nil a) := by
cases as with
| nil => rfl
| snoc _ _ => simp; unfold concat concat; rfl
/-! ## Initial Sequences -/
/--
Takes the first `k` entries from an `LTuple` to form a new `LTuple`, or the
entire `LTuple` if `k` exceeds the size.
-/
def take (t : LTuple α n) (k : Nat) : LTuple α (min n k) :=
if h : n ≤ k then
cast (by rw [min_eq_left h]) t
else
match t with
| nil => nil
| @snoc _ n' as a => cast (by rw [min_lt_succ_eq h]) (take as k)
where
min_lt_succ_eq {m : Nat} (h : ¬m + 1 ≤ k) : min m k = min (m + 1) k := by
have h' : k + 1 ≤ m + 1 := Nat.lt_of_not_le h
simp at h'
rw [min_eq_right h', min_eq_right (Nat.le_trans h' (Nat.le_succ m))]
/--
Taking no entries from any `LTuple` should yield an empty `LTuple`.
-/
theorem self_take_zero_eq_nil (t : LTuple α n) : take t 0 = @nil α := by
induction t with
| nil => simp; rfl
| snoc as a ih => unfold take; simp; rw [ih]; simp
/--
Taking any number of entries from an empty `LTuple` should yield an empty
`LTuple`.
-/
theorem nil_take_zero_eq_nil (k : Nat) : (take (@nil α) k) = @nil α := by
cases k <;> (unfold take; simp)
/--
Taking `n` entries from an `LTuple` of size `n` should yield the same `LTuple`.
-/
theorem self_take_size_eq_self (t : LTuple α n) : take t n = t := by
cases t with
| nil => simp; rfl
| snoc as a => unfold take; simp
/--
Taking `n - 1` elements from an `LTuple` of size `n` yields the same result,
regardless of the last entry's value.
-/
theorem take_subst_last {as : LTuple α n} (a₁ a₂ : α)
: take (snoc as a₁) n = take (snoc as a₂) n := by
unfold take
simp
/--
Taking `n` elements from an `LTuple` of size `n + 1` is the same as invoking
`init`.
-/
theorem init_eq_take_pred (t : LTuple α (n + 1)) : take t n = init t := by
cases t with
| snoc as a =>
unfold init take
simp
rw [self_take_size_eq_self]
simp
/--
If two `LTuple`s are equal, then any initial sequences of these two `LTuple`s
are also equal.
-/
theorem eq_tuple_eq_take {t₁ t₂ : LTuple α n}
: (t₁ = t₂) → (t₁.take k = t₂.take k) := by
intro h
rw [h]
/--
Given an `LTuple` of size `k`, concatenating an arbitrary `LTuple` and taking
`k` elements yields the original `LTuple`.
-/
theorem eq_take_concat {t₁ : LTuple α m} {t₂ : LTuple α n}
: take (concat t₁ t₂) m = t₁ := by
induction t₂ with
| nil =>
simp
rw [self_concat_nil_eq_self, self_take_size_eq_self]
| @snoc n' as a ih =>
simp
rw [concat_snoc_snoc_concat]
unfold take
simp
rw [ih]
simp
end LTuple